You think you're confused? Even clinicians say drug names are misleading. Issue 12 (13th November 2018) - Knopf, Alison
Abstract : Clinicians are used to the names of psychotropic medications — so used to them that they may forget how odd they sound to patients and parents. In an article in the October issue of the Journal of the American Academy of Child and Adolescent Psychopharmacology, top researchers in the field write that the medication names are actually unclear and misleading, and propose a new nomenclature.